Pendidikan Multikultural Berbantuan Metode Pictorial Riddle Untuk Meningkatkan Karakter Kreatif dan Bersahabat Siswa Kelas 3 Sekolah Dasar - Ika Ari Pratiwi; Siti Masfuah; Wawan Shokib Rondli (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2018)
The differences in social, religious, and cultural status make an impact on social attitudes, the cooperative systems, and how to make friends in school. Efforts to harmonize and unify the diversity of students in schools today is integrated with multicultural education. The purpose of this research is to describe the effectiveness of multicultural education implementation with the help of pictorial riddle method to increase the value of creativity, and friendly/communicative character. In this research, the application of multicultural education is carried out in thematic integrated learning of social and natural science in grade 3 semester 2. The quasi experiment design with control group used pre-test and post-test. The result showed that multicultural education, aided with pictorial riddle method increased the value of creative and friendly/communicative character. The creative character in the experimental class increased significantly from the pretest score of 69 to 85 in the posttest, with the gain of 0.53 in the medium criterion. The increase of friendly/communicative value in the pretest experimental class was 70, increased to 80 at posttest, with the gain of 0,31 in medium criterion.